Otosclerosis and Stapes Surgery 2007
DOI: 10.1159/000098861
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve in Stapes Surgery and Its Implication for Training

Abstract: This is a mismatch of trainers and trainees in stapes surgery. If the current trend of decline in stapes surgery continues, it will take many years for some otolaryngologists to complete their learning curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 0 publications
3
36
0
2
Order By: Relevance
“…This finding is consistent with studies of stapedectomy which demonstrated that approximately 60-100 cases were necessary for surgeons to reach full skill and comfort with this otologic procedure, [11][12][13] except that in our study the trend toward increased efficiency continued beyond 100 procedures. In the current study there was a substantial population of cases that did not fit this inverse correlation of surgeon experience and surgical time; instead, there were numerous instances of long surgical duration despite considerable surgeon volume.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with studies of stapedectomy which demonstrated that approximately 60-100 cases were necessary for surgeons to reach full skill and comfort with this otologic procedure, [11][12][13] except that in our study the trend toward increased efficiency continued beyond 100 procedures. In the current study there was a substantial population of cases that did not fit this inverse correlation of surgeon experience and surgical time; instead, there were numerous instances of long surgical duration despite considerable surgeon volume.…”
Section: Discussionsupporting
confidence: 92%
“…A sensorineural hearing loss is also possible in the event of incorrect surgical procedures. These possible complications, the microscopic field, and the complex anatomy of the middle ear are a cause of concern and indecision for young inexperienced surgeons [29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The residency-training program should provide a long period of instruction during which the trainee acquires adequate surgical skills and anatomical knowledge to carefully perform stapes surgery [29][30][31][32] . Therefore, achieving surgical competency in this kind of surgery represents a challenge to both the trainee and trainer.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the procedure and experience of the surgeon, the learning curve can be as few as ≤ 10 procedures, as in the case of minimally invasive total knee arthroplasty, or > 80 procedures for other types of surgery. 24,35 Specifically in neurosurgery, Nowitzke 28 defined the learning curve of microendoscopic discectomy at ~ 30 procedures, after which time the operative time and complications have stabilized. McLoughlin and Fourney 25 described the learning curve of the minimally invasive microdiscectomy to be ~ 15 cases, suggesting that the 15-case difference may be related to Nowitzke's use of the endoscope, which is often unfamiliar to practicing neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%